Multiple classification of flower images using transfer learning - Cengil, Emine; Cinar, Ahmet (Institute of Electrical and Electronics Engineers Inc., 2019)
Deep learning technologies have been successful in many fields in recent years. Image classification problem is one of the areas where the use of the results is successful. The study draws attention to the use of pretrained models in problem solving. With the approach called transfer learning, frequently used pretrained deep learning models such as Alexnet, Googlenet, VGG16, DenseNet and ResNet are used for image classification. The results show that the models used achieve acceptable performance rates while the highest performance is achieved with the VGG16 model. © 2019 IEEE.
2019 International Conference on Artificial Intelligence and Data Processing Symposium, IDAP 2019 -- 21 September 2019 through 22 September 2019 -- Malatya -- 153040
Keywords: Convolutional Neural Networks; Deep Learning; Image Classification; Transfer Learning